Arthroscopic Partial Repair of Irreparable, Massive Rotator Cuff Tears - Castricini, Roberto (Arthrosc Tech, 2017)
Several treatment options for chronic, massive rotator cuff tears exist, and they include debridement with possible biceps tenotomy or tenodesis, open or arthroscopic partial repair, muscle or tendon transfer, superior capsule reconstruction, synthetic patch augmentation, and reverse total shoulder arthroplasty. The aim of this technique article is to describe our preferred surgical option for irreparable, massive rotator cuff tears with an irreparable supraspinatus, a reparable infraspinatus, and an intact or reparable subscapularis tendon.